Adsorbent for aromatic hydrocarbon separation and preparation method and application thereof
By using adsorbents composed of nickel, rare earth metals and alumina, the existing adsorbents are solved, and the efficient and rapid aromatic separation effect is achieved.
Patent Information
- Application Number
- CN202311222164.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-21
AI Technical Summary
The existing adsorbents used for aromatic hydrocarbon separation have problems such as slow adsorption speed, low aromatic separation efficiency, poor adsorption performance or complicated preparation processes.
The adsorbents with nickel, rare earth metals and carrier alumina are used as the main components. Through the acid amount of weak acid, medium and strong acid, strong acid ternary distribution and metal ions, the specific surface area and pore size distribution of the adsorbent are improved, and its adsorption performance is enhanced.
It has achieved efficient separation of aromatic hydrocarbons in raw oil, with significant advantages of high adsorption rate and large adsorption amount, and can effectively separate bicyclic aromatic hydrocarbons.
Smart Images

Figure CN119657068A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adsorbents, and in particular relates to an adsorbent for aromatic hydrocarbon separation, a preparation method and application thereof. Background Art
[0002] The distillation range of diesel is 180-350℃, and the carbon number distribution is 12-15. It mainly comes from ethylene cracking units, catalytic reforming units and coal tar units, etc. Its chemical composition is complex, including chain alkanes, cycloalkanes, aromatics and organic sulfur and nitrogen compounds. The cetane number of diesel is closely related to its chemical composition. The cetane number of normal alkanes is the highest, followed by isoalkanes, monocyclic alkanes and monocyclic aromatics are in the middle, and the cetane number of condensed ring alkanes and condensed ring aromatics is the lowest. The aromatic content in catalytic diesel is as high as more than 60wt%, of which dicyclic and tricyclic aromatics account for about 75wt% of the total aromatics. The high content of condensed ring aromatics is the main reason for the low cetane number of catalytic diesel. The utilization of condensed ring aromatics is the key to improving the quality of catalytic diesel products.
[0003] The separation of aromatics in diesel, especially the separation of polycyclic aromatic hydrocarbons, has always been a hot topic in petrochemical research. The separation of polycyclic aromatic hydrocarbons in diesel can be regarded as the separation of aromatics and aliphatic hydrocarbons in diesel. Hydrofining has high efficiency in removing aromatics, but the reaction conditions are high temperature and high pressure, the process flow is long, and the equipment investment is large. Among separation technologies, adsorption separation has the advantages of high efficiency, reversible process, short process, and no hazardous waste generation, which has attracted the attention of scientific researchers. Adsorption separation relies on the chemical complexation between the adsorbent and the adsorbed substance for separation. The adsorption separation efficiency is closely related to the structure of the adsorbent.
[0004] CN 105289466 B discloses an adsorbent for separating polycyclic aromatic hydrocarbons from diesel by adsorption. The adsorbent is prepared from sodium silicate and inorganic acid to obtain a silicon-containing carrier, and metal elements such as transition metals and alkaline earth metals are added for modification. Using simulated diesel with a polycyclic aromatic hydrocarbon content of 17.2wt% as raw material, the polycyclic aromatic hydrocarbon removal rate can reach 83.95%. CN109022020B discloses a method for multi-component adsorption separation of diesel, which uses two 16-24 column simulated moving bed adsorption devices connected in series, using molecular sieves such as SAPO-11 and Na-ZSM-11 as shape-selective adsorbents, and using metal-modified MCM-41 molecular sieves as aromatic hydrocarbon adsorbents, which can achieve the separation of paraffins, cycloalkanes, monocyclic aromatic hydrocarbons and dicyclic aromatic hydrocarbons. CN106140078B discloses a method for preparing a bimetallic aromatic adsorbent, which uses silicon oxide as a carrier, loads alkaline earth metals and transition metals as active components, and uses high-boiling point aromatic solvent oil with a distillation range of 150-300°C as a raw material. The aromatic removal rate can reach 95%.
[0005] Existing adsorbents for aromatic separation are mainly molecular sieves and active metal-loaded silica carriers. The adsorbents in the prior art have problems such as slow adsorption speed, low aromatic separation efficiency, poor adsorption performance or complicated preparation process to varying degrees. Therefore, it is of great significance to develop an adsorbent suitable for aromatic separation. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an adsorbent for separation of aromatics and a preparation method and application thereof. The adsorbent is used for separation of aromatics in crude oil, can effectively separate aromatics in crude oil, and has the significant advantages of high adsorption rate and large adsorption amount.
[0007] The first aspect of the present invention provides an adsorbent for separation of aromatic hydrocarbons. The adsorbent, in parts by weight, comprises:
[0008] 2.0 to 20.0 parts of nickel, preferably 7.0 to 14.0 parts of nickel;
[0009] 0.3 to 2.0 parts of rare earth metals;
[0010] 72.0 to 97.1 parts of carrier alumina, preferably 79.7 to 90.7 parts of carrier alumina.
[0011] According to the present invention, the acid content of the adsorbent presents a ternary distribution of weak acid, medium-strong acid and strong acid. Further, the acid content of weak acid: the acid content of medium-strong acid: the acid content of strong acid = 100: 5-20: 15-35.
[0012] According to the present invention, the order of the acidity of the adsorbent is: weak acid > strong acid > medium-strong acid.
[0013] According to the present invention, the rare earth metal includes at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium, preferably at least one of lanthanum, cerium, europium and praseodymium.
[0014] According to the present invention, the adsorbent is in the shape of a clover leaf.
[0015] According to the present invention, the adsorbent has a diameter of 1 to 3 mm.
[0016] According to the present invention, the specific surface area of the adsorbent is 270 to 350 m 2 / g; the pore volume of the adsorbent is 0.6~0.9cm 3 / g; the most probable pore size of the adsorbent is 8 to 13 nm.
[0017] The second aspect of the present invention provides a method for preparing the adsorbent. The preparation method comprises the following steps:
[0018] (1) forming alumina raw powder and performing a first calcination to obtain the alumina carrier;
[0019] (2) An impregnation solution containing a nickel source, a rare earth metal source, a first auxiliary agent, and a second auxiliary agent is impregnated into an alumina carrier, and then dried and calcined for a second time to obtain the adsorbent.
[0020] According to the present invention, the alumina raw powder in step (1) has a minimum pore size of 10 to 13 nm and a specific surface area of 300 to 350 m 2 / g; pore volume is 0.8~1.0cm 3 / g.
[0021] According to the present invention, the conditions for the first calcination in step (1) are: a calcination temperature of 500 to 700° C. and a calcination time of 4 to 8 hours.
[0022] According to the present invention, before the molding of the alumina raw powder in step (1), an auxiliary agent and / or an acidic solution may be added. The auxiliary agent includes at least one of sesbania powder, methylcellulose, polyethylene glycol, calcium nitrate, and potassium nitrate. The acidic solution includes at least one of nitric acid, phosphoric acid, acetic acid, hydrogen chloride, and tartaric acid. The mass ratio of the auxiliary agent to the amount of alumina raw powder added is 2:100 to 6:100; the mass ratio of the acidic solution to the amount of alumina raw powder added is 2:100 to 15:100. During the molding process, an appropriate amount of water may be added as needed. The mass ratio of the amount of water added to the amount of alumina raw powder added is 80:100 to 120:100.
[0023] According to the present invention, the molding process in step (1) is performed by kneading and extruding.
[0024] According to the present invention, drying can be performed before the first roasting in step (1). The drying conditions are: drying temperature of 105-120° C. and drying time of 10-16 hours.
[0025] According to the present invention, in step (2), the first auxiliary agent comprises at least one of citric acid, tartaric acid, dimethylglyoxime, ethylenediaminetetraacetic acid (EDTA), aminotriacetic acid (also known as nitrilotriacetic acid NTA), diethylenetriaminepentaacetic acid (DTPA) and salts thereof. The mass ratio of the amount of the first auxiliary agent added to the nickel source in terms of nickel is 0.05 to 0.4, preferably 0.1 to 0.4.
[0026] According to the present invention, in step (2), the second auxiliary agent includes at least one of dodecyl dimethyl benzyl ammonium chloride, sodium N-dodecyl ethylenediamine triacetate (NaLED3A), and sodium N-dodecyl ethylenediamine triacetate (LED3A). The mass ratio of the amount of the second auxiliary agent added to the nickel source in terms of nickel is 0.05 to 0.4, preferably 0.1 to 0.4.
[0027] According to the present invention, the nickel source in step (2) is a nickel salt; further, the nickel source includes at least one of basic nickel carbonate, nickel nitrate and nickel acetate.
[0028] According to the present invention, the rare earth metal source in step (2) is a rare earth metal salt; further, the rare earth metal salt is at least one of a nitrate and a chloride containing a rare earth metal.
[0029] According to the present invention, the impregnation in step (2) is an equal volume impregnation. In the impregnation solution, the amount of water added is 2 to 10 times the mass of the nickel source added.
[0030] According to the present invention, the drying conditions in step (2) are: drying temperature 105-120° C.; drying time 10-16 hours.
[0031] According to the present invention, the conditions of the second calcination in step (2) are: calcination temperature 200-450°C, preferably 200-400°C; calcination time 4-8h. After the calcination, the first auxiliary agent and the second auxiliary agent are completely thermally decomposed, and nickel and rare earth metals can be evenly dispersed.
[0032] The third aspect of the present invention provides the use of the adsorbent in separation of aromatic hydrocarbons. The use can effectively separate aromatic hydrocarbons from crude oil.
[0033] According to the present invention, in the application, the raw oil is diesel. The distillation range of the raw oil is 170°C to 240°C. The content of aromatics is 10wt% to 60wt%; the content of non-aromatics is 40wt% to 90wt%. Furthermore, the content of bicyclic aromatics is 8wt% to 58wt%.
[0034] According to the present invention, in the application, the mass ratio of the feedstock oil to the adsorbent is 3:1 to 5:1.
[0035] Compared with the prior art, the present invention has significant advantages and outstanding effects, mainly as follows:
[0036] (1) The adsorbent of the present invention comprises 2.0 to 20.0 parts of nickel; 0.3 to 2.0 parts of rare earth metal; 72.0 to 97.1 parts of carrier alumina, and the acid content of the adsorbent presents a ternary distribution of weak acid, medium-strong acid, and strong acid; wherein the acid content of strong acid: the acid content of medium-strong acid: the acid content of weak acid = 100: 5 to 20: 15 to 35. The adsorbent has a high specific surface area, a suitable pore size distribution, and a suitable acid distribution. The acid center of the carrier can accept the electrons of aromatic hydrocarbons, and the empty d orbital of the loaded metal can coordinate with the π bond orbital of aromatic hydrocarbons, thereby promoting the adsorption process of aromatic hydrocarbons and increasing the adsorption amount.
[0037] The adsorbent of the present invention has a suitable pore size distribution, which is beneficial to the diffusion of aromatic hydrocarbons in the pores of the adsorbent and accelerates the physical adsorption process.
[0038] (2) The adsorption of adsorbents is divided into physical adsorption and chemical adsorption. The chemical adsorption of adsorbents is usually stronger than physical adsorption. The alumina carrier of the present invention provides a certain Lewis acid center. The Lewis acid center acts as an electron acceptor, and the benzene ring in the aromatic hydrocarbon acts as an electron donor. The coordination and complexation between the two is conducive to the adsorption of aromatic hydrocarbons. The greater the electron cloud density of aromatic hydrocarbons, the easier it is to be adsorbed. The present invention loads active metal ions Ni on the alumina carrier. 2+ and rare earth metals such as La 3+ . The loaded nickel ions and rare earth metal ions have empty 3d orbitals, which can accept electrons from the outside world, coordinate with the π bond orbitals of aromatic hydrocarbons, form dp bonding, and are also beneficial to the adsorption of aromatic hydrocarbons; while the non-aromatic hydrocarbons in the crude oil, especially aliphatic hydrocarbons, do not have empty π orbitals. At the same time, nickel and rare earth metals will produce a synergistic effect, and the adsorption performance will be improved after the addition of rare earth metals. The inventors have found through research that the acidic center of the carrier can accept electrons from aromatic hydrocarbons, and the empty d orbitals of the loaded metals can coordinate with the π bond orbitals of aromatic hydrocarbons, which can accelerate the adsorption process of aromatic hydrocarbons and increase the adsorption amount. Under the dual effects of alumina carrier and active metals, there are obvious differences in the adsorption rates of aromatic hydrocarbons and non-aromatic hydrocarbons, especially aliphatic hydrocarbons, and adsorbents. Therefore, the adsorbent of the present invention can achieve the separation of aromatic hydrocarbons in diesel.
[0039] In the preparation method of the adsorbent of the present invention, the calcination temperature is controlled in the preparation of the alumina carrier to adjust the acidity of the alumina carrier in step (1). And in step (2), the first auxiliary agent and the second auxiliary agent are added to the impregnation solution, and the auxiliary agents can weaken the competitive interaction of the hydroxyl groups on the surface of the alumina, complex with the metal ions through chelation, and thermally decompose in the subsequent calcination process, so that the nickel and rare earth metal components can be evenly dispersed, achieving the purpose of atomic-level dispersion, which is conducive to forming an active phase at a lower temperature, and can further adjust the acidity distribution of the adsorbent to obtain an adsorbent with a suitable acidity distribution.
[0040] In the preparation method of the adsorbent of the present invention, alumina powder with large pores and high specific surface area is used as raw material, and the prepared alumina carrier has a high specific surface area and is conducive to the adsorption of aromatic hydrocarbons on the inner and outer surfaces of the adsorbent.
[0041] (3) In the application of the adsorbent of the present invention, the adsorbent can effectively adsorb aromatic hydrocarbons, especially bicyclic aromatic hydrocarbons, in the diesel fraction, and has the advantages of high adsorption rate and large adsorption amount. The static saturated adsorption amount of aromatic hydrocarbons of the adsorbent of the present invention is greater than 0.10 g / g adsorbent, and the initial adsorption rate is greater than 0.014 g / (min / g adsorbent). BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1XRD spectra of the alumina raw powder, alumina carrier (Comparative Example 1) and adsorbent in Example 1.
[0043] Figure 2 The pore size distribution diagram of the alumina raw powder, alumina carrier (Comparative Example 1) and adsorbent in Example 1.
[0044] Figure 3 NH3-TPD spectra of Example 1, Example 3 and Comparative Example 4. DETAILED DESCRIPTION
[0045] The present invention will be described in detail below in conjunction with specific embodiments. The specific implementation methods described herein are used to illustrate and explain the present invention, but are not intended to limit the present invention.
[0046] In the present invention, each example uses model diesel as a raw material for adsorption evaluation, the distillation range of the model diesel is 185° C. to 220° C., the aromatic content is 57.38 wt %, and the non-aromatic content is 42.62 wt %.
[0047] In the present invention, the performance evaluation method of each adsorbent is as follows: an adsorption experiment is carried out under the conditions of 20°C and normal pressure, the mass ratio of raw material to adsorbent is 5:1, the adsorbent is immersed in the raw material and stirred continuously to make it fully contacted, and the stirring speed is selected as 300r / min. Sampling is continuously taken as the reaction time passes, and the content of each component in the raw material and the product is determined by gas chromatography, and the adsorption amount and adsorption rate are calculated.
[0048]
[0049] M1, M2: the mass of model diesel before and after adsorption experiment,
[0050] c1, c2: mass fraction of aromatics in the model diesel before and after the adsorption experiment,
[0051] M0: mass of adsorbent.
[0052] In the present invention, the chromatographic analysis adopts a GC-2010plus gas chromatograph of Shimadzu Corporation of Japan, a DM-WAX chromatographic column, 60m×0.25mm×0.5μm, and a hydrogen flame detector. N2 is used as a carrier gas, and the injection volume is 0.6μL. The chromatographic column adopts a programmed temperature rise, and after the room temperature is raised to 50°C and stayed for 3min, the temperature is raised to 240°C at a rate of 10°C / min and stayed for 5min.
[0053] In the present invention, the acid content of the adsorbent is tested using a programmed temperature ammonia adsorption instrument produced by Tianjin Pengxiang Technology Co., Ltd. Test method The test conditions are that the sample is pretreated with N2 at 550°C for 60 minutes, adsorbs ammonia for 30 minutes after cooling to room temperature, and then desorbs in a N2 atmosphere. According to the NH3-TPD spectrum, the spectrum has a low-temperature desorption zone of 100-400°C and does not contain 400°C, a medium-temperature desorption zone of 400-530°C, and a high-temperature desorption zone>530°C, each of which has a desorption peak. The desorption peak in the low-temperature desorption zone represents the desorption of NH3 from the weak acid site on the surface of the adsorbent, corresponding to the weak acid center of the adsorbent. The desorption peak in the medium-temperature desorption zone represents the desorption of NH3 from the medium-strong acid site on the surface of the adsorbent, corresponding to the medium-strong acid center of the adsorbent. The desorption peak in the high-temperature desorption zone represents the desorption of NH3 from the strong acid site on the surface of the adsorbent, corresponding to the strong acid center of the adsorbent. The NH3-TPD spectrum was fitted with a Gaussian curve, and the ratios of the strong acid content, medium-strong acid content, and weak acid content of the adsorbent were calculated based on the peak areas of the weak acid peak, medium-strong acid peak, and strong acid peak.
[0054] In the present invention, XRD is measured using a D8Advance X-ray powder diffractometer from Bruker, Germany, with an operating current of 30 mA and an operating voltage of 30 kV. Experimental conditions: scanning with Cu Kα (λ=1.54 nm) rays, with a scanning range of 5-50°.
[0055] In the present invention, the specific surface area, pore volume, most probable pore size, and pore size distribution are measured using a Tristar-3000 fully automatic specific surface and porosity analyzer from Micromeritics Instruments, Inc. Pretreatment conditions: vacuum degassing at 300°C for 4 hours, followed by N2 physical isothermal adsorption measurement, and specific surface area and pore distribution are calculated using the BET method and the BJH method.
[0056] In the present invention, Table 1 shows the pore structure properties of the adsorbent. Table 2 shows the acid amount distribution of the adsorbent and the evaluation results of the adsorbent.
[0057] [Example 1]
[0058] (1) Carrier preparation: Weigh 200 g of alumina powder and 5.6 g of sesbania powder, 4.8 g of nitric acid, and 200 g of deionized water, knead and extrude into strips, dry at 110°C for 12 h, and calcine at 550°C for 4 h to obtain an alumina carrier. The properties of the alumina powder are as follows: the specific surface area is 318.47 m 2 / g, pore volume is 0.84cm 3 / g, and the most probable pore diameter is 10.61m.
[0059] (2) Loading active metals: 12.9 g nickel nitrate, 1.32 g cerium chloride, 1 g citric acid, 1 g dodecyl dimethyl benzyl ammonium chloride, and 100 g deionized water to form an impregnation solution; weigh 100 g of the above alumina carrier and spray the impregnation solution evenly on the carrier. After the impregnation, dry at 110°C for 12 h and calcine at 280°C for 4 h to obtain an adsorbent.
[0060] The adsorbent is in the shape of a clover leaf, and the diameter of the adsorbent is 2 mm. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Ce, and 96.2 parts of Al2O3.
[0061] The XRD spectrum of the adsorbent is shown in Figure 1 Specific surface area, pore volume and pore size distribution are shown in Figure 2 and Table 2; NH3-TPD spectrum see Figure 3 .
[0062] Depend on Figure 1 It can be seen that the XRD spectra of the adsorbent and the alumina carrier are similar, and no new diffraction peaks appear after loading nickel and rare earth metals, indicating that the metals are evenly dispersed on the carrier surface. Figure 2 As shown in Table 2, the specific surface area of the adsorbent is 312.45 m 2 / g, pore size 0.89cm 3 / g, the pore size distribution is single-pore distribution, and the most probable pore size is 9.95nm. Figure 3 It can be seen that the acid content of the adsorbent presents a ternary distribution of weak acid, medium-strong acid, and strong acid, and the acid content of weak acid: the acid content of medium-strong acid: the acid content of strong acid = 100:12:27.
[0063] (3) Adsorption evaluation: 100 g of model diesel and 20 g of dehydrated activated adsorbent were weighed and aromatic adsorption experiments were carried out in a constant temperature continuous stirring device at 20 °C, atmospheric pressure and a stirring rate of 300 r / min. Samples were continuously taken during the adsorption process. The adsorption evaluation results are shown in Table 2.
[0064] [Example 2]
[0065] (1) Carrier preparation: Same as Example 1.
[0066] (2) Loading active metals: 51.6 g nickel nitrate, 1.32 g cerium chloride, 1 g citric acid, 1 g sodium N-dodecylethylenediaminetriacetate (NaLED3A), and the rest is the same as in Example 1. The composition of the adsorbent is: 9.4 parts of Ni, 0.4 parts of Ce, and 87.5 parts of Al2O3.
[0067] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0068] [Example 3]
[0069] (1) Carrier preparation: calcined at 680°C for 4 h, the rest is the same as in Example 1.
[0070] (2) Loading active metal: the same as in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Ce, and 96.2 parts of Al2O3.
[0071] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0072] [Example 4]
[0073] (1) Carrier preparation: Same as Example 1.
[0074] (2) Loading active metal: calcined at 360°C for 4 hours, the rest is the same as in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Ce, and 96.2 parts of Al2O3.
[0075] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0076] [Example 5]
[0077] (1) Carrier preparation: Same as Example 1.
[0078] (2) Loading active metals: 12.9 g nickel nitrate, 0.92 g lanthanum chloride, 1 g citric acid, 1 g sodium N-dodecylethylenediaminetriacetate (NaLED3A), and the rest is the same as in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of La, and 96.2 parts of Al2O3.
[0079] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0080] [Example 6]
[0081] (1) Carrier preparation: Same as Example 1.
[0082] (2) Loading active metals: 12.9 g nickel nitrate, 1.54 g praseodymium nitrate, 1 g citric acid, 1 g sodium N-dodecylethylenediaminetriacetate (NaLED3A), and the rest is the same as in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Pr, and 96.2 parts of Al2O3.
[0083] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0084] [Example 7]
[0085] (1) Carrier preparation: Same as Example 1.
[0086] (2) Loading active metals: 12.9 g nickel nitrate, 0.87 g neodymium chloride, 1 g citric acid, 1 g sodium N-dodecylethylenediaminetriacetate (NaLED3A), and the rest is the same as in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Nd, and 96.2 parts of Al2O3.
[0087] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0088] [Comparative Example 1]
[0089] Carrier preparation: Weigh 200g of alumina powder and 5.6g of sesbania powder, 4.8g of nitric acid, and 200g of deionized water, knead and extrude, dry at 110°C for 12h, and calcine at 550°C for 4h to obtain an alumina carrier. The properties of the alumina powder are as follows: the specific surface area is 318.47m 2 / g, pore volume is 0.84cm 3 / g, and the most probable pore diameter is 10.61m.
[0090] The adsorption evaluation conditions are the same as those in Example 1. The adsorption evaluation results of the alumina carrier in this example are shown in Table 2.
[0091] [Comparative Example 2]
[0092] (1) Carrier preparation: Same as Example 1.
[0093] (2) Loading active metal: Except for not adding cerium chloride, other conditions are the same as those in Example 1. The composition of the adsorbent is: 2.5 parts of Ni and 96.2 parts of Al2O3.
[0094] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0095] [Comparative Example 3]
[0096] (1) Carrier preparation: Same as Example 1.
[0097] (2) Loading active metal: 5.8 g nickel nitrate, 0.5 g cerium chloride, other conditions are the same as in Example 1. The composition of the adsorbent is: 1.2 parts of Ni, 0.2 parts of Ce, and 96.2 parts of Al2O3.
[0098] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0099] [Comparative Example 4]
[0100] (1) Carrier preparation: calcined at 750°C for 4 h, other conditions were the same as in Example 1.
[0101] (2) Loading active metal: the same as in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Ce, and 96.2 parts of Al2O3.
[0102] (3) Adsorption evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0103] [Comparative Example 5]
[0104] (1) Carrier preparation: Same as Example 1.
[0105] (2) Loading active metals: Except for not adding citric acid and dodecyl dimethyl benzyl ammonium chloride, the other conditions are the same as those in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Ce, and 96.2 parts of Al2O3.
[0106] (3) Adsorbent evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0107] [Comparative Example 6]
[0108] (1) Carrier preparation: Same as Example 1.
[0109] (2) Loading active metals: The first auxiliary agent is citric acid in an amount of 1 g; the second auxiliary agent is 1-hydroxyethylidene-1,1-diphosphonic acid (HEDPA) in an amount of 1 g; the other conditions are the same as those in Example 1. The composition of the adsorbent is: 2.5 parts of Ni, 0.5 parts of Ce, and 96.2 parts of Al2O3.
[0110] (3) Adsorbent evaluation: Same as Example 1. The adsorption evaluation results are shown in Table 2.
[0111] Table 1 Pore structure properties of adsorbents
[0112]
[0113]
[0114] Table 2 Acidity distribution of adsorbents and adsorption evaluation results
[0115]
[0116] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An adsorbent for separation of aromatic hydrocarbons, comprising, by weight: 2.0 to 20.0 parts of nickel; 0.3 to 2.0 parts of rare earth metals; 72.0 to 97.1 parts of carrier alumina; The acid content of the adsorbent presents a ternary distribution of weak acid, medium-strong acid and strong acid; wherein the acid content of weak acid: the acid content of medium-strong acid: the acid content of strong acid = 100: 5-20: 15-35.
2. The adsorbent according to claim 1, characterized in that: The order of acidity is: weak acid > strong acid > moderately strong acid.
3. The adsorbent according to claim 1, characterized in that: The rare earth metal includes at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium, preferably at least one of lanthanum, cerium, europium and praseodymium.
4. The adsorbent according to claim 1, characterized in that: The specific surface area of the adsorbent is 270 to 350 m 2 / g; and / or, the pore volume of the adsorbent is 0.6 to 0.9 cm 3 / g; and / or, the most probable pore size of the adsorbent is 8 to 13 nm.
5. A method for preparing the adsorbent according to any one of claims 1 to 4, comprising the following steps: (1) forming alumina raw powder and performing a first calcination to obtain the alumina carrier; (2) An impregnation solution containing a nickel source, a rare earth metal source, a first auxiliary agent, and a second auxiliary agent is impregnated into an alumina carrier, and then dried and calcined for a second time to obtain the adsorbent.
6. The preparation method according to claim 5, characterized in that: The first auxiliary agent in step (2) includes at least one of citric acid, tartaric acid, dimethylglyoxime, ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid and salts thereof; and / or, the mass ratio of the amount of the first auxiliary agent added in step (2) to the nickel source in terms of nickel is 0.05 to 0.4, preferably 0.1 to 0.
4.
7. The preparation method according to claim 5 or 6, characterized in that: The second auxiliary agent in step (2) includes at least one of dodecyldimethylbenzyl ammonium chloride, sodium N-dodecylethylenediaminetriacetate, and sodium N-dodecylethylenediaminetriacetate; and / or, the mass ratio of the amount of the second auxiliary agent added in step (2) to the nickel source in terms of nickel is 0.05 to 0.4, preferably 0.1 to 0.
4.
8. The preparation method according to claim 5, characterized in that: The conditions for the second calcination in step (2) are: calcination temperature of 200-450°C, preferably 200-400°C, and calcination time of 4-8h; and / or, the conditions for the first calcination in step (1) are: calcination temperature of 500-700°C, and calcination time of 4-8h.
9. The preparation method according to claim 5, characterized in that: The alumina raw powder of step (1) has a minimum pore size of 10 to 13 nm; and / or a specific surface area of 300 to 350 m 2 / g; and / or, a pore volume of 0.8 to 1.0 cm 3 / g.
10. Use of the adsorbent according to any one of claims 1 to 4 or the adsorbent prepared by the preparation method according to any one of claims 5 to 9 in separation of aromatic hydrocarbons.
Citation Information
Patent Citations
An adsorbent for the adsorption and separation of polycyclic aromatic hydrocarbons in diesel oil and its preparation method
CN105289466B
A method for preparing a bimetallic aromatic hydrocarbon adsorbent
CN106140078B
A method for adsorption separation of multiple components in diesel fuel
CN109022020B
Bimetallic mineral spirit refining adsorbent and preparation method and application thereof
CN103752266A
Mineral spirit refining adsorbent and preparation method thereof
CN103752271A